2020
DOI: 10.1371/journal.pone.0232219
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical factors for non-hospital deaths among cancer patients: A nationwide population-based cohort study

Abstract: Background Factors associated with place of death inform policies with respect to allocating end-of-life care resources and tailoring supportive measures. Objective To determine factors associated with non-hospital deaths among cancer patients. Design Retrospective cohort study of cancer decedents, examining factors associated with nonhospital deaths using multinomial logistic regression with hospital deaths as the reference category. Setting/subjects Cancer patients (n = 15254) in Singapore who died during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
15
2
Order By: Relevance
“…This indicates that while some gains have been made, opportunities for further improvement remain. In contrast to studies from other countries, Canadian in-hospital death rates remain higher than those in the United States, but are similar to those in Taiwan and Singapore, and lower than those in Norway [ 22 , 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 78%
“…This indicates that while some gains have been made, opportunities for further improvement remain. In contrast to studies from other countries, Canadian in-hospital death rates remain higher than those in the United States, but are similar to those in Taiwan and Singapore, and lower than those in Norway [ 22 , 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 78%
“…There is an increased rate of hospitalisation toward the end of life of cancer patients. Studies have found that about half of cancer-related deaths occurred in acute hospitals (36)(37)(38). While the reasons for admission were not captured in our study, it would not be unreasonable to infer that the inpatients were more symptomatic and required a higher level of care that could not be administered in the outpatient setting.…”
Section: Development Of the Nccs Prognostic Modelmentioning
confidence: 75%
“…The burden of cancer continues to increase worldwide. According to the World Health Organization (WHO), cancer is the second leading cause of death in the world, accounting for approximately 9.6 million deaths in 2018 [34]. Numerous studies suggest that redox imbalance may be a factor predisposing to cancer development [9,35,36].…”
Section: Discussionmentioning
confidence: 99%